High Entropy Oxide Ceramics for Future Aerospace Thermal Barriers - Aronkytö, Ville (My University, 2025)
Thermal protection systems (TPS) are critical components in aerospace engineering, In re-entry vehicles (RVs) where extreme thermal and mechanical stresses occur during atmospheric re-entry. Contemporary TPS materials, such as reinforced carbon-carbon (RCC) and silica-based ceramics, have served well in the past missions to space. However, future aerospace applications demand enhanced thermal resistance, reusability, and environmental durability from the TPS. This thesis explores the potential of high entropy oxide ceramics (HEOCs) as next-generation thermal barrier materials. HEOCs are a class of materials composed of multiple elements in near-equimolar ratios, leading to high entropy and stabilization of single-phase structures. These materials exhibit unique properties, including thermal stability (up to ~1600 °C), low thermal conductivity and improved mechanical performance due to entropy-driven effects, such as lattice distortion, cocktail effect and sluggish diffusion effects. A comparative analysis of selected HEOCs, particularly rare-earth zirconates and aluminium-based garnets was conducted against contemporary TPS materials. This highlighted their potential from moderate to high temperatures in aerospace environments depending on further application in the field. The findings suggest that although HEOCs may not yet match the extreme temperature thresholds of current materials like the RCC, but the HEOCs studied exhibited a combination of thermal insulation, mechanical robustness, and structural tunability ranking them as promising candidates for future reusable thermal barrier applications.

Lämpösuojajärjestelmät (TPS) ovat kriittisiä komponentteja ilmailu- ja avaruustekniikassa, erityisesti paluualuksissa (RV), joissa äärimmäisiä olosuhteita ilmakehään paluun aikana. Nykyiset TPS-materiaalit, kuten vahvistettu hiili-hiili-komposiitti (RCC) ja piipohjaiset keraamit ovat toimineet hyvin aikaisemmissa avaruuslennoissa. Tulevaisuuden avaruussovellukset vaativat kuitenkin entistä parempaa lämmönkestävyyttä, uudelleenkäytettävyyttä ja ympäristön sietokykyä näiltä TPS-materiaaleilta. Tämä opinnäytetyö tutkii korkean entropian oksidikeraamien (HEOC) potentiaalia seuraavan sukupolven lämpösuojamateriaaleina. HEOC -materiaalit koostuvat useista alkuaineista täysin tai lähes yhtä suurina määrinä, mikä johtaa korkeaan entropiaan ja yhden faasin rakenteiden stabiloitumiseen. Näillä materiaaleilla on ainutlaatuisia ominaisuuksia, kuten lämmönkestävyys (jopa noin 1600 °C), alhainen lämmönjohtavuus ja parantunut mekaaninen suorituskyky, jotka johtuvat entropiavaikutteisista ilmiöistä. Näitä ilmiöitä ovat muiden muassa hilavääristymä, niin sanottu “cocktail-efekti” ja hidas diffuusio. Valittuja HEOC-materiaaleja – erityisesti harvinaisten maametallien zirkonaatteja ja alumiinipohjaisia granaatteja – verrattiin nykyisiin TPS-materiaaleihin. Vertailu toi esiin niiden potentiaalin, josta ilmeni mahdollinen käyttö kohtalaisen korkeisiin lämpötiloihin avaruusympäristöissä, sovelluksesta riippuen. Tulokset viittaavat siihen, että vaikka HEOC-materiaalit eivät vielä yllä nykyisten materiaalien, kuten RCC:n, äärimmäisiin lämpötilankestoihin, tutkimuksessa tarkastellut HEOC:t osoittivat yhdistelmän lämmöneristävyyttä, mekaanista kestävyyttä ja rakenteellista muokattavuutta, mikä tekee niistä tulevaisuuden kannalta erittäin lupaavia ehdokkaita tuleviin lämpösuojasovelluksiin.
Keywords: High entropy oxide ceramics (HEOCs), Thermal protection systems (TPS), re-entry vehicles, thermal barriers, high entropy oxide, high entropy effect